Pregunta
upstudy study bank question image url

5. When the expression \( x^{3}+p x^{2}+2 x+1 \) is divided by \( (x-2) \), the remainder is thrice the remainder when the divisor is \( (x+1) \). Find the value of \( p \). [Answer Key] \( p=-19 \)

Ask by Adkins Park. in Singapore
Mar 20,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

\( p = -19 \)

Solución

Given the polynomial \[ f(x) = x^3 + p x^2 + 2x + 1, \] we first find the remainders when the polynomial is divided by \( (x-2) \) and \( (x+1) \). **Step 1.** When dividing by \( (x-2) \), the remainder is \( f(2) \): \[ f(2) = 2^3 + p \cdot 2^2 + 2(2) + 1 = 8 + 4p + 4 + 1 = 4p + 13. \] **Step 2.** When dividing by \( (x+1) \), the remainder is \( f(-1) \): \[ f(-1) = (-1)^3 + p \cdot (-1)^2 + 2(-1) + 1 = -1 + p - 2 + 1 = p - 2. \] **Step 3.** According to the problem, the remainder when divided by \( (x-2) \) is thrice the remainder when divided by \( (x+1) \). Thus, we have: \[ 4p + 13 = 3(p - 2). \] **Step 4.** Solve the equation step by step: \[ 4p + 13 = 3p - 6. \] Subtract \( 3p \) from both sides: \[ p + 13 = -6. \] Subtract 13 from both sides: \[ p = -19. \] So, the value of \( p \) is: \[ \boxed{-19}. \]

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Extra Insights

To solve the problem, we will use the Remainder Theorem, which states that the remainder of the division of a polynomial \( f(x) \) by a linear divisor \( (x - a) \) is \( f(a) \). First, we calculate the remainders when the polynomial \( f(x) = x^3 + px^2 + 2x + 1 \) is evaluated at \( x = 2 \) and \( x = -1 \): 1. **Calculating \( f(2) \)**: \[ f(2) = 2^3 + p(2^2) + 2(2) + 1 = 8 + 4p + 4 + 1 = 4p + 13 \] 2. **Calculating \( f(-1) \)**: \[ f(-1) = (-1)^3 + p(-1)^2 + 2(-1) + 1 = -1 + p - 2 + 1 = p - 2 \] According to the problem, the remainder when dividing by \( (x-2) \) is three times the remainder when dividing by \( (x+1) \). Therefore, we have the equation: \[ 4p + 13 = 3(p - 2) \] Expanding the right side: \[ 4p + 13 = 3p - 6 \] Now, we rearrange the equation to isolate \( p \): \[ 4p - 3p = -6 - 13 \implies p = -19 \] Thus, the value of \( p \) is \( -19 \).

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad